2010
DOI: 10.3171/2010.5.spine09906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sexual dysfunction before and after surgery for lumbar disc herniation

Abstract: Object Sexuality is an important aspect of human life. Sexual activity may be affected in lumbar disc herniation through different mechanisms. The aim of this study is to evaluate patients' sexual problems and sexual behavior patterns before and after surgical treatment of lumbar disc herniation. Methods Forty-three patients were included in the study (mean age 41.4 years). A visual analog scale, the Oswestry Disability Index, the Hospital Anxiety and Depression Scale, and a sexuality assessment questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 13 publications
1
38
0
4
Order By: Relevance
“…Pain and discomfort during sex life reported by patients presented statistically significant differences between the groups. Other authors [14][15][16][17] also observed that the more patients suffered in their sex life, the higher ODI and VAS scores they obtained, but according to these studies this dysfunction is caused by psychological disorders rather than physical impairment [18,19].…”
Section: Discussionmentioning
confidence: 93%
“…Pain and discomfort during sex life reported by patients presented statistically significant differences between the groups. Other authors [14][15][16][17] also observed that the more patients suffered in their sex life, the higher ODI and VAS scores they obtained, but according to these studies this dysfunction is caused by psychological disorders rather than physical impairment [18,19].…”
Section: Discussionmentioning
confidence: 93%
“…Chronic back pain has been shown to have negative consequences on sexual function, which can contribute to a deterioration in quality of life. 1–4 Previous studies have evaluated sexual function in patients with chronic pain, cardiac disease, and rheumatic conditions, and hip arthritis, 2,5,6 and some have evaluated sexual function in patients undergoing spinal surgery. 1,79 These studies show that sexual function is generally improved postoperatively when compared to preoperative function.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 Previous studies have evaluated sexual function in patients with chronic pain, cardiac disease, and rheumatic conditions, and hip arthritis, 2,5,6 and some have evaluated sexual function in patients undergoing spinal surgery. 1,79 These studies show that sexual function is generally improved postoperatively when compared to preoperative function. However, these studies were comprised of a small sample size, lacked a non-operative control group and focused on intervertebral disk herniation 1 , total disk replacement 7 , anterior spinal surgery 8 , and thoracolumbar fusion to the pelvis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many health care practitioners are not inclined to discuss the sexual needs of their clients [10], despite the fact that their patients consider their sexuality to be an important domain that is never discussed in relation to their condition [6]. Many sexologists agree that concerns with regard to sexual activity should be addressed by the health care practitioner and advice on coital movement and position adjustments would lead to improvements in sexual activity [4][5][6].…”
Section: Introductionmentioning
confidence: 95%
“…The potential effect of low back pain (LBP) on sexual activity has been recognized and incorporated into one of the most commonly recommended condition-specific outcome measures for spinal disorders: the Oswestry disability index (ODI) [3]. The influence that sexual activity has on QoL, health, and disability has important implications for women who experience LBP; between 48 [4] and 73 [5] percent of women with LBP have reported a marked reduction in the frequency of their sexual activity.…”
Section: Introductionmentioning
confidence: 99%